Hermeneutical Discourse of Interpretation by KH. Sya’roni Ahmadi on YouTube Channel - Muhammad Afnan Abdillah (QOF, 2023)
Technological developments have an impact on almost every aspect of human life. It  was responded well by religious leaders, including in Islamic da'wah. KH Sya'roni Ahmadi is one of the Kudus scholars who utilizes YouTube-based technological developments as a medium for delivering commentary material. This paper aimed to reveal his model of interpretation, and to see how far he understands the audience textually and contextually. The author uses the virtual ethnography method, which is a method to reach the audience's interaction life on the YouTube page. The results of this study indicated that KH Sya'roni Ahmadi uses the tahlili or sequential method in conveying commentary material. He really understands the social conditions in society and the heterogeneity of the Majlis Tafsir congregation. Therefore the character of KH Sya'roni Ahmadi's preaching has transitional gradations, starting from being hard, firm to soft and straightforward. In addition, by presenting elaborative exegesis material, he explained coherently in depth starting from the point of view of the science of qiroat, then entering the exegesis material correlated with the context when the interpretation was delivered.